CODE ADMINISTRATIVE OFFENCE (NEW WORDING) OBJECT VOLUME AND IN THE CONTEXT OF ADMINISTRATIVE LEGISLATION REFORM “OFFICIAL PERSON” NOTION - Shishimbayeva , Сауле Сериккановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article views some aspects new redaction of Code administrative offence, standing Cod’s problems and theirs decision ways